Compreendendo a cultura on-line das mulheres portadoras de Doença Trofoblástica Gestacional (DTG) - Diniz, Marisa Victoria [UNIFESP] (2019)
Objective: This study aims to understand and evaluate the efficiency of social assistance and support process received by women with gestational Trophoblastic Disease (GTD) from the Brazilian Association of Gestational Trophblastic Disease (BAGTD) group mediated by a social network called Facebook®. Furthermore, to conclude if the behavior differs according to the place of treatment (performed in Reference Centers in GTD or other places). Methodology: Methods of cross-sectional, netnographic study with quantitative and qualitative approach of translational vision. Initially, an interpretative and investigative observation was performed for cultural behavior on the online community through users of Facebook® network of BAGTD group, analyzing the pattern of interaction among patients as well as between patients and physicians. In the next step, the group members were invited to respond to an online questionnaire divided into three modules: internet-related, history of disease and socioeconomic profile, but with criteria for inclusion of having been diagnosed with GTD at some point in their life and residing in Brazil for treatment. The variables were analyzed in a descriptive way by means of immersion in the social network context analyzed with the data that were collected by the questionnaire using Google Docs and Microsoft Excel. The responses were divided into two groups for statistical analysis: treated in reference center (PRC) and not treated in a reference center (PNRC). Quantitative variables were analyzed using mean, standard deviation, median, minimum and maximum, and the total observation were valid. Comparison between quantitative data was performed using the non-parametric Mann-Whitney test. Qualitative variables were analyzed using frequency and percentage. xv To compare the groups, for the qualitative variables, the chi-square test, the Fisher's exact test or the likelihood ratio were used, as indicated. The level of significance was established as P <05 for all tests. Statistical analysis was conducted using the IBM SPSS Statistics version 22 program (IBM Corp., New York, USA). Results: It was verified through an investigative process that of 5.783 members total, 807 were GTD patients and eligible to participate in the study, 367 answered the questionnaire. Eleven patients, non-Brazilian residents, were excluded and the final sample consisted of 44.1% of total patients (356/807). The demographic characteristics of FBBAGTD patients showed no difference. The analysis of socioeconomic characteristics PNRC had higher educational level. Of the total, 89% (317/356) of the patients accessed the cell phone internet preferably from their homes. Facebook® and WhatsApp® were the most used social networks by patients (327/356, 92%). Instagram was more commonly used by PNCR (114/180) than by PRC (92/176, P = .03). The interest groups of these patients on Facebook® were those who provided answers to their questions about the disease and treatment options (246/356, 69%) and that provided exchange of experiences among people who had a similar problem or interest (274 / 367, 77%). PNRCs found the FBBAGTD through Web searches (139/180 vs 85/176, P <.001) while CRP more frequently were indicated by the attending RC physicians to access the FBBAGTD (64/176 vs 32/180, P < .001). PNRC patients accessed the FBBAGTD for a time greater than 6 months (118/180 vs 95/176, P = .03;) and raised more questions about DTG treatment (107/180) than CRP (84/176, P =.01. Conclusion: The FBBAGTD acts as an important support tool for patients, considering the credibility that patients declared to have in the guidelines given by the group's physicians. GTD Patients, who were not treated at Reference Centers, had a longer FBBADTG period and more questions about the disease.